Psychological skill configurations and rehabilitation readiness among injured pencak silat athletes: A person-centered analysis - Edi Purnomo; Heny Setyawati; Agus Kristiyanto; Donny Wira Yudha Kusuma; Nadia Ingrida Kusumadewi (CV. FOUNDAE, 2026)
Background: Psychological responses to sport injury critically determine rehabilitation engagement and return-to-sport outcomes. Existing research has predominantly employed variable-centered approaches that obscure heterogeneity in athletes' psychological adaptation, particularly within culturally embedded combat sports such as Pencak Silat. Aims: This study aimed to identify distinct psychological profiles among injured Pencak Silat athletes empirically and to examine how these profiles relate to rehabilitation readiness, thereby advancing an evidence-based framework for psychological skills training in injury rehabilitation contexts. Methods: A quasi-experimental pretest–posttest design combined with a person-centered analytical framework was employed. Data were collected from 108 injured Pencak Silat athletes across nine secondary educational institutions. Latent Profile Analysis (LPA) was conducted on five psychological domains: anxiety regulation, coping skills, self-confidence, motivation, and rehabilitation readiness, followed by MANOVA and hierarchical regression to examine profile-based differences and predictive relationships. Results: Three distinct profiles, Vulnerable (n = 29), Adaptive (n = 46), and Resilient (n = 33), were identified. All psychological indicators differed significantly across profiles, with large effect sizes. Hierarchical regression demonstrated that psychological skills and profile membership accounted for significant variance in rehabilitation readiness beyond injury-related factors (ΔR² = .19). Conclusion: Psychological adaptation to sport injury is best conceptualized through profile-based configurations of psychological skills. These findings support the development of individualized, profile-informed psychological skills training to enhance rehabilitation readiness and sustainable return-to-sport outcomes in Pencak Silat athletes.